The role of synbiotics as adjunctive therapy in prolonging latency period in Preterm Premature Rupture of Membranes - Donel S; Amiruddin Hidayatullah; Maya Savira (Majalah Obstetri & Ginekologi, 2026)
HIGHLIGHTS Synbiotics significantly prolonged the latency period in women with preterm premature rupture of membranes (PPROM). The intervention group receiving synbiotics showed a longer latency period (>7 days) compared to the control group (OR = 9.53, p = 0.0126). The study supports the potential use of synbiotics as an adjunctive therapy to improve perinatal outcomes in PPROM cases. ABSTRACT Objective: Preterm Premature Rupture of Membranes (PPROM) is one of the main causes of preterm birth, significantly contributing to perinatal morbidity and mortality. This study aims to evaluate the effect of synbiotic administration on prolonging the latency period in pregnant women with preterm premature rupture of membranes (PPROM). The research explores whether synbiotics, a combination of probiotics and prebiotics, can modulate the inflammatory response and extend the latency period, potentially improving perinatal outcomes in PPROM cases. Materials and Methods: This randomized controlled trial was conducted at Arifin Achmad Hospital and other affiliated hospitals in Pekanbaru, Indonesia. A total of 32 pregnant women diagnosed with preterm premature rupture of membranes (PPROM) were enrolled and randomly assigned into two groups: the control group, which received cefotaxime and placebo, and the intervention group, which received cefotaxime and synbiotics. The primary outcome was the latency period, defined as the time from PPROM to delivery. Data were analyzed using SPSS version 25, with a significance level set at p < 0.05. Results: A total of 32 pregnant women diagnosed with PPROM were enrolled in the study. The control group (n=16) received cefotaxime and placebo, while the intervention group (n=16) received cefotaxime and synbiotics. The latency period was significantly longer in the intervention group (>7 days) compared to that in the control group (OR = 9.53; p = 0.0126). Conclusion: Synbiotics can be an effective adjunct therapy in prolonging the latency period in preterm premature rupture of membranes (PPROM), potentially reducing the risk of preterm birth.